1994
DOI: 10.3109/10731199409117870
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hemoglobin-Dependent Neurotoxicity: Alpha-Alpha Crosslinked Hemoglobin

Abstract: Adult human hemoglobin A0 (HbA0) has been shown to be neurotoxic, and we wish to report on similar studies conducted using a modified hemoglobin, which has been crosslinked between the alpha subunits (alpha-alpha Hb). Cortical cell cultures were prepared from fetal Swiss-Webster mice at 15-16 days gestation. Mature cultures (days in vitro, 12-16) were exposed to alpha-alpha Hb in a defined medium for 24-48 hours at 37 degrees C. Low micromolar amounts of alpha-alpha Hb were neurotoxic in a concentration-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…This finding is interestingly different to that reported for the interaction between 30 40 these proteins and hydrogen peroxide where the a-DBBF derivative consistently showed greater sensitivity to breakdown than HbAo [7,21]. It has recently been suggested that the cycling between the ferric and ferryl haem of a number of modified anges In the Soret region haemoglobins in the presence of hydrogen peroxide can result in tude changes upon carbon an apparent peroxidase activity and that this activity is sensitive to structural modifications of the protein [8,39]. Haemoglobin is also able to catalyse the oxidation of unsaturated fatty acids, such as phosphatidylcholine [40].…”
mentioning
confidence: 57%
“…This finding is interestingly different to that reported for the interaction between 30 40 these proteins and hydrogen peroxide where the a-DBBF derivative consistently showed greater sensitivity to breakdown than HbAo [7,21]. It has recently been suggested that the cycling between the ferric and ferryl haem of a number of modified anges In the Soret region haemoglobins in the presence of hydrogen peroxide can result in tude changes upon carbon an apparent peroxidase activity and that this activity is sensitive to structural modifications of the protein [8,39]. Haemoglobin is also able to catalyse the oxidation of unsaturated fatty acids, such as phosphatidylcholine [40].…”
mentioning
confidence: 57%
“…Many, but not all, HBOCs are also bound by Hp, although the strength of binding varies, depending on the particular modifi cation chemistry utilized (Bunn 1967, Lockhart and Smith 1975, Benesch et al 1976, Panter et al 1994, Ship et al 2005, Schaer et al 2006, Buehler et al 2008, Baek et al 2012, Jia et al 2013. Th ese complexes are taken up by the liver, as are the much higher doses of free HBOC which are more representative of the anticipated clinical uses of these formulations (Bleeker et al 1989, Keipert et al 1989b, Smith et al 1990, Dittmer et al 1992, Hsia et al 1993, Bush et al 1994, Keipert et al 1994, Ship et al 2005, Baek et al 2012.…”
Section: Overview Of Distribution and Plasma Eliminationmentioning
confidence: 97%
“…Apart from low plasma levels of Hp and hemopexin, most Hb chemical modification procedures may decrease or eliminate the binding properties of Hb to Hp (19–21). Moreover, some chemical modification procedures, by altering Hb autoxidation kinetics and other related redox characteristics, may destabilize the heme‐globin binding force and increase the release of heme (22,23).…”
Section: Hemoglobin Clearancementioning
confidence: 99%